Formation of the Charge‐Localized Dimer Radical Cation of 2‐Ethyl‐9, 10‐dimethoxyanthracene in Solution Phase. Issue 21 (20th March 2019) - Choi, Jungkweon; Ahn, Doo‐Sik; Fujitsuka, Mamoru; Tojo, Sachiko; Ihee, Hyotcherl; Majima, Tetsuro
Abstract: Although dimer radical ions of aromatic molecules in the liquid‐solution phase have been intensely studied, the understanding of charge‐localized dimers, in which the extra charge is localized in a single monomer unit instead of being shared between two monomer units, is still elusive. In this study, the formation of a charge‐localized dimer radical cation of 2‐ethyl‐9, 10‐dimethoxyanthracene (DMA), (DMA)2 .+ is investigated by transient absorption (TA) and time‐resolved resonance Raman (TR 3 ) spectroscopic methods combined with a pulse radiolysis technique. Visible‐ and near‐IR TA signals in highly concentrated DMA solutions supported the formation of non‐covalent (DMA)2 .+ by association of DMA and DMA .+ . TR 3 spectra obtained from 30 ns to 300 μs time delays showed that the major bands are quite similar to those of DMA except for small transient bands, even at 30 ns time delay, suggesting that the positive charge of non‐covalent (DMA)2 .+ is localized in a single monomer unit. From DFT calculations for (DMA)2 .+, our TR 3 spectra showed the best agreement with the calculated Raman spectrum of charge‐localized edge‐to‐face T‐shaped (DMA)2 .+, termed DT .+, although the charge‐delocalized asymmetric π‐stacked face‐to‐face (DMA)2 .+, termed DF3 .+, is the most stable structure of (DMA)2 .+ according to the energetics from DFT calculations. The calculated potential energy curves for the association between DMA .+ and DMA showed that DT .+ is likely to be efficiently formed and contribute significantly to the TR 3 spectra as a result of the permanent charge‐induced Coulombic interactions and a dynamic equilibrium between charge localized and delocalized structures. Abstract : Charge‐induced dimer radical cations were generated by pulse radiolysis of 2‐ethyl‐9, 10‐dimethoxyanthracene in solution. The formation of non‐covalent charge‐localized dimer radical cations was characterized by time‐resolved spectroscopic methods and DFT calculations.